Effect of three collections of Tithonia diversifolia on the ruminal microbial population of cattle - Galindo, Juana; González, Niurca; Ruíz, T.; Herrera, Magaly; Moreira, Onidia; Capó, Aned; Díaz, Humberto (Cuban Journal of Agricultural Science, 2022)
In order to determine the effect of three collections of Tithonia diversifolia (mv-12, mv-14 and mv-17), collected in the eastern region of Cuba, on the ruminal microbial population of cattle, an experiment under in vitro conditions was developed. The control treatments with Cynodon nlemfuensis (star grass) were compared: star grass + mv-12; star grass + mv-14 and star grass + mv-17. The three collections were included at a rate of 20 % of the dry matter. The crude protein content was 19-23 % of the dry matter. With the materials mv-14 and mv-17 higher populations of cellulolytic bacteria were obtained, at three and six hours after starting fermentation with respect to that obtained with star grass. The three collections doubled the population of proteolytic bacteria three hours after starting fermentation, while at six hours only mv-12 produced effects in this bacterial group. The methane values were 37.4, 32.6, 33.2 and 32.33 g/kg of digested organic matter for the control, and the treatments mv-12, mv-14 and mv-17, respectively. Although they did not differ between plant materials, mv-12, mv-14 and mv-17 produced less methane than the star grass treatment only (P = 0.0477). It is concluded that the treatments mv-12, mv-14 and mv-17 caused modifications in the ruminal ecosystem, by increasing the population of total cellulolytic organisms and proteolytic bacteria; in addition to reducing the protozoan population. The methane estimated from crude protein concentration also decreased. Key words: cellulolytic bacteria, proteolytic, methane, SCFAs, protozoa